If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 10h = 7h + 6 Reorder the terms: -3 + 10h = 6 + 7h Solving -3 + 10h = 6 + 7h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-7h' to each side of the equation. -3 + 10h + -7h = 6 + 7h + -7h Combine like terms: 10h + -7h = 3h -3 + 3h = 6 + 7h + -7h Combine like terms: 7h + -7h = 0 -3 + 3h = 6 + 0 -3 + 3h = 6 Add '3' to each side of the equation. -3 + 3 + 3h = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 3h = 6 + 3 3h = 6 + 3 Combine like terms: 6 + 3 = 9 3h = 9 Divide each side by '3'. h = 3 Simplifying h = 3
| (9x-8)+x=180 | | (3a+2)=-8 | | -9x+y=-22 | | 8b+8=6b | | x+3x-4=6 | | 2lne^5=y | | 7x+54+42=180 | | 0.60x=12 | | 9s=-1+10s | | -6+5w=6w | | -26=-6+4v | | -8t-2=-9t | | 3x^2-32x=-65 | | x+.25x=75 | | 2x-1=1.7 | | 2x^2+20x+70=0 | | Ptanx+qtanx=tanz | | 9x-4+122=180 | | (8+3)4=8*4+3*4 | | 45j+-36j-3j-45=-87 | | (4x-22)+(10x-4)+(x+11)=180 | | -8a+14b+61=0 | | 2z-z+2z-z-2=18 | | 3x+7y=-10 | | (9x+3)+(5x-2)+(11x-21)=180 | | 6x+3+75=90 | | 2a-a-a+3a-3=18 | | 1/8(4,200) | | 28x+14y=2 | | 3s-3s+s+1=13 | | 6x(2x+7)=48 | | 10j-j-2j=7 |